2019
DOI: 10.1101/762237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of Serum Neurofilament Light Chain as a Biomarker of Parkinson’s Disease Progression

Abstract: Background: Alterations in neurofilament light chain (NfL), reflecting axonal damage, have been proposed as a biomarker for neurological disorders including Parkinson's disease (PD). Methods:We measured NfL concentrations by immunoassay in (1) a set of longitudinal CSF samples from 82 PD, 14 other neurodegenerative disorders (OND), and 53 healthy controls (HC);(2) A cross-sectional cohort with paired CSF and serum samples from subjects with 151 PD, 344 OND, and 20 HC, and (3a) a large longitudinal validation c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…As expected, PD patients showed motor and cognitive compromise with respect to controls and also had alterations in common biomarkers of neural damage . High‐risk CLU patients showed both a quantitative (lower MoCA scores) and qualitative (higher prevalence of clinically diagnosed PD‐MCI or PDD) cognitive decline at follow‐up.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As expected, PD patients showed motor and cognitive compromise with respect to controls and also had alterations in common biomarkers of neural damage . High‐risk CLU patients showed both a quantitative (lower MoCA scores) and qualitative (higher prevalence of clinically diagnosed PD‐MCI or PDD) cognitive decline at follow‐up.…”
Section: Discussionsupporting
confidence: 60%
“…16,17 As expected, PD patients showed motor and cognitive compromise with respect to controls and also had alterations in common biomarkers of neural damage. 18,19 High-risk CLU patients showed both a quantitative (lower MoCA scores) and qualitative (higher prevalence of clinically diagnosed PD-MCI or PDD) cognitive decline at follow-up. Further characterization of this cognitive compromise revealed both frontal and posterior-cortical relative deficits with respect to the low-risk CLU group.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the neurofilament proteins, neurofilament light (NfL) chain has been recognized as a possible marker of axonal injury in various neurological disorders [1], including multiple sclerosis [2], motor neurone disease [3,4], frontotemporal dementia spectrum disorders [5,6], traumatic brain injury [7], and cerebrovascular disease [8]. In Parkinson's disease (PD), blood NfL has been reported to be higher in cases vs controls [9,10], and shown to be able to distinguish PD from atypical PD (APD) [11,12]. NfL has also been found to associate with longer disease duration, more aggravated motor symptoms [11], and correlate with motor and/or cognitive decline [13] in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Neurofilament light chain (NfL), a highly expressed protein in large caliber myelinated axons, has been recently proposed as general marker of neuronal degeneration and damage in different neurological disorders [7,8]. In fact, CSF and plasma NfL levels are significantly altered in Alzheimer’s disease (AD), prion diseases, amyotrophic lateral sclerosis, frontotemporal dementia, whereas findings in Parkinson’s disease (PD) and early DLB were contradictory [9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, CSF and plasma NfL levels are significantly altered in Alzheimer’s disease (AD), prion diseases, amyotrophic lateral sclerosis, frontotemporal dementia, whereas findings in Parkinson’s disease (PD) and early DLB were contradictory [9]. In addition to that, it has been reported that plasma and CSF NfL levels correlated with disease severity and progression in PD [8,10,11] and Alzheimer’s disease [12]. Very few studies have focused on DLB patients and, to the best of our knowledge, no prospective longitudinal studies evaluated plasma NfL as potential early diagnostic and prognostic marker in DLB.…”
Section: Introductionmentioning
confidence: 99%